Are you a cheeseburger? - Arnaldo, Monica (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2021)
Grub is a lonely raccoon. Looking for food. Seed is, well, a seed! Hoping someone will plant it. When the two finally meet, they realize they might be able to help each other! Could Seed grow Grub's favorite food, mouthwatering cheeseburgers? Seed isn't sure what a cheeseburger is exactly, but... maybe!
Keywords: Cheeseburgers -- Juvenile fiction; Raccoon -- Juvenile fiction; Seeds -- Juvenile fiction; Helping behavior -- Juvenile fiction; Nocturnal animals -- Fiction; Helpfulness -- Fiction; Flowers -- Fiction; Picture books